Spatiotemporal Patterns in Profiles of Amino Acids Indicates They Are Unlikely Singular Olfactory Cues Underlying Natal Homing in Migratory Fishes - Kimmel, Jacob; Buchinger, Tyler; Tamrakar, Sonam; Huerta, Belinda; Larson, Douglas; Baker, Edward; Zorn, Troy; Scribner, Kim; Li, Weiming (Freshwater Biology, 2025)
ABSTRACT Migratory fishes are renowned for their ability to home to natal streams for spawning. Learned olfactory cues play a critical role in natal homing of Pacific salmon and other fishes, but the underlying chemical signature of streams remains poorly understood after decades of study. The molecules that convey a stream‐specific odour must differ among sites but remain constant over time. Among leading odorant candidates are amino acids; however, little research has assessed the spatial and temporal variability of amino acid profiles in streams. We report a comprehensive chemical study of dissolved amino acids as potential olfactory cues for homing by migratory fish. Specifically, we profiled amino acids in water from 23 streams in the upper Laurentian Great Lakes basin over 2 years. We investigated variation in amino acid profiles (1) among regions and rivers within a year, (2) between years and (3) among sites and across the seasons of migration and early life history within a stream. Liquid‐chromatography tandem mass spectrometry revealed nanomolar concentrations for most of the 20 L‐amino acids measured, above the levels detectable by studied migratory fishes. Moreover, amino acid profiles were temporally stable between 2 years and across an annual season from adult spawning migration through offspring early‐life development within a stream. However, spatial differences in amino acid profiles were evident primarily over large geographic distances (among regions) but not among tributaries within regions or among sites within a stream. Collectively, our results indicate dissolved amino acids may be consistent components of rivers' odorant profiles but suggest additional molecules are likely important for natal homing of migratory fishes to specific spawning sites. We suggest that future studies consider the combined importance of amino acids and molecules from other chemical classes. Understanding the chemical basis of olfactory‐guided natal homing is especially important as human activities could alter the odorant profiles of streams and thereby disrupt fish migrations and negatively impact population recruitment.
Keywords: Biology; Ecology; Evolutionary biology; Great Lakes; Homing (biology); Neuroscience; Olfaction; Olfactory cues; Olfactory system; Zoology; dept.che; navigation; olfactory imprinting; peer-reviewed; site fidelity; sturgeon